THE STRUCTURE OF Mn(III)-Salen COMPLEX WITH CHLORIDE AND HEXAFLUOROPHOSPHATE ANIONS - Siti Khairunnisa Bustaman, Irna
Manganese(III) salen complex is an interesting research topic due to the outer electron configuration 3d4 of manganese(III) which is relatively less stable species that can be stabilized by salen as a tetradentate ligand. Generally, the complex is made from manganese(II) acetate or chloride salt reacted with salen-H2 ligand in alcoholic solvent under atmospheric condition. The complex formed has chemical formula of [Mn(III)salen-OAc] or [Mn(III)salen-Cl] with square pyramide geometry and OAc?/Cl? in the axial position. OAc?/Cl? group was previously reported able to be replaced by other anions, such as N(CN)2?, N3? ?, Ag(CN)2?. Adding a neutral ligand 4-aminopyridine (4-apy) to [Mn(III)salen-OAc] complex was not able to replace OAc? anion. However, following by PF6? anion addition, the OAc? can be replaced leading to two molecules of 4-apy coordinated to manganese(III) and consequently PF6? becomes the counter anion. This phenomenon can only be observed through single crystal X-ray diffraction (XRD) technique. Therefore, this research examined the addition of pyrazine as a neutral ligand to [Mn(III)salen-Cl] complex. Based on single crystal XRD analysis, the complex has chemical formula of [Mn(III)salen(H2O)Cl].CH3OH. This structure is monomeric with orthorhombic crystal system. The yield obtained was 75-80% with magnetic moment 5.4 BM. According to the structure, it is found that addition of pyrazine to the reaction can not replace Cl? at axial position of Mn(III)salen complex. After the addition of PF6?, the Cl? is not coordinated anymore to the Mn(III)salen and the complex has final formula of [Mn(III)2(salen)2(H2O)2][Mn(III)salen(H2O)2]2[PF6]4.2H2O which formed monomeric and dimeric cationic complex mixtures. The compound has octahedral geometry with monoclinic crystal system. 55-64% yield was obtained with magnetic moment of 5.1 BM. Based on single crystal XRD analysis, pyrazine is uncoordinated to manganese(III) in both of the complexes.